Unveiling the Hidden Allies in the Fight Against Antimicrobial Resistance—Medicinal Plant Endophytes - Adeoye J. Kayode; Aboi Igwaran; Folasade Banji-Onisile; Nneka A. Akwu; John O. Unuofin; Ayodeji C. Osunla; Samson O. Egbewale; Hery Purnobasuki (Bacteria)
Medicinal plants have long been a vital source of various natural products in the form of pure compounds or standardized extracts. The World Health Organization estimated that 80% of populations in Africa, Asia, and Latin America rely on traditional medicine for primary health care. In recent decades, endophytic microorganisms living within plants have gained attention for their ability to produce bioactive compounds with significant therapeutic potential. This review explores the diversity of medicinal plant endophytes, focusing on their pharmacological significance, including antimicrobial, anticancer, antidiabetic, and antioxidant properties. Additionally, we discuss the application of nanotechnology and computational tools in enhancing the potency and screening of endophyte-derived metabolites. Despite the promising potential, challenges such as scalability, safety, and commercial viability remain. Future research should prioritize optimizing production, elucidating biosynthetic pathways, and integrating advanced technologies to effectively harness these bioactive compounds for novel drug development.